2021
DOI: 10.1101/2021.10.22.465479
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Coordinated DNA and Histone Dynamics Drive Accurate Histone H2A.Z Exchange

Abstract: Nucleosomal histone H2A is exchanged for its variant H2A.Z by the SWR1 chromatin remodeler, but the mechanism and timing of histone exchange remain unclear. Here, we quantify DNA and histone dynamics during histone exchange in real-time using a three-color single-molecule FRET assay. We show that SWR1 operates with timed precision to unwrap DNA with large displacement from one face of the nucleosome, remove H2A-H2B from the same face, and rewrap DNA, all within 2.3 seconds. Such productive DNA unwrapping requ… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 64 publications
(74 reference statements)
0
3
0
Order By: Relevance
“…The affinity of SWR1 for nucleosomes is enhanced by both long linker DNA (Ranjan et al ., 2013; Yen et al, 2013) and histone acetylation (Zhang et al, 2005), and both factors play a role in the recruitment of SWR1 to promoters. A recent single molecule study further showed that SWR1 likely exploits preferential interactions with long-linker length DNA by demonstrating that H2A.Z is predominantly deposited on the long-linker distal face of the nucleosome (Poyton et al, 2021), similar to what is observed in vivo (Rhee et al, 2014). It is possible that SWR1 first binds long-linker DNA and then finds its target, the +1 nucleosome, using facilitated diffusion ( Figure 1A ), as was previously suggested (Ranjan et al ., 2013).…”
Section: Introductionmentioning
confidence: 80%
See 2 more Smart Citations
“…The affinity of SWR1 for nucleosomes is enhanced by both long linker DNA (Ranjan et al ., 2013; Yen et al, 2013) and histone acetylation (Zhang et al, 2005), and both factors play a role in the recruitment of SWR1 to promoters. A recent single molecule study further showed that SWR1 likely exploits preferential interactions with long-linker length DNA by demonstrating that H2A.Z is predominantly deposited on the long-linker distal face of the nucleosome (Poyton et al, 2021), similar to what is observed in vivo (Rhee et al, 2014). It is possible that SWR1 first binds long-linker DNA and then finds its target, the +1 nucleosome, using facilitated diffusion ( Figure 1A ), as was previously suggested (Ranjan et al ., 2013).…”
Section: Introductionmentioning
confidence: 80%
“…near the center of an average NDR of ∼150 bp) our findings suggest that SWR1 would require 46 milliseconds (see Materials and Methods ) to scan and encounter a flanking nucleosome by 1D diffusion at 0.024 μm 2 /sec. A recent report shows that when complexed with a canonical nucleosome and the H2A.Z-H2B dimer, SWR1 can rapidly perform the ATP hydrolysis-dependent histone exchange reaction, which occurs on average in 2.4 seconds as measured by an in vitro single molecule FRET assay (Poyton et al, 2021). Thus, SWR1-catalyzed histone H2A.Z exchange on chromatin may be an intrinsically rapid event that occurs on a timescale of seconds.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation